Genetic diversity and structure of creole cattle (Bos taurus) from southern Peruvian Highlands - Figueroa Venegas, Deyanira Antonella (2024)
The creole cattle was originated after the introduction of cattle into America 5 centuries ago. Currently, the production traits of Peruvian creole cattle is scarcely known. An important characteristic of the creole cattle is its adaptability to different extreme environments. However, to date, molecular studies in Peruvian creole cattle are still scarce. Currently, due to the advances in molecular genetics, a new generation of molecular markers has been developed for the genetic characterization of livestock. Single nucleotide polymorphisms (SNP) have become a very popular tool for the genetic study of livestock populations. Genome-wide SNP chips were developed for multi-breed genetic studies in cattle.